From Mediated Fieldwork to Co-Constructed Partnerships: A Framework for Guiding and Reflecting on P-12 School–University Partnerships. (January 2020) - Burroughs, Greer; Lewis, Amy; Battey, Dan; Curran, Mary; Hyland, Nora E.; Ryan, Sharon
An essential component of teacher preparation is clinical practice that allows teacher candidates (TCs) to observe, reflect upon, test their ideas, and adjust and improve their methods in classrooms. Weaknesses in the structure and organization between coursework and clinical practice in teacher preparation programs often present barriers from fully achieving these goals. University–school partnerships have the potential to overcome these challenges and create spaces for mutually beneficial learning opportunities for all stakeholders. In this article, we identify six levels to illustrate the continua of work with schools in the preparation of TCs that describe how a program might move from current partnership practice to the kinds of partnership practice described by McDonald and colleagues and the Council for the Accreditation of Educator Preparation (CAEP). While developing partnerships with schools is work that has inherent challenges, the potential of this work to meaningfully transform the preparation of teachers is crucial.